Cross Creek - Rawlings, Marjorie Kinnan, 1896-1953.; Steenburgen, Mary.; Thorn EMI Films; Thorn EMI Video (Firm) (New York : Thorn EMI Video, 1983)
After ten years as a frustrated newspaper reporter and unsuccessful author of fiction, Marjorie Rawlings turns her back on financial security and takes up residence in the unknown and wholly-alien culture of the Florida Everglades. In this remote, wild and untamed portion of central Florida, Rawlings is inspired to create a gallery of unforgettable characters and to produce critically-acclaimed best sellers.
VHS format.
"TVA 2184"
Based on Marjorie Kinnan Rawlings memoirs' Cross Creek.
Videocassette release of the 1983 motion picture by Thorn EMI Films.
Producer, Robert B. Radnitz ; director, Martin Ritt ; screenplay, Darlene Young ; music, Leonard Rosenman.
Mary Steenburgen, Rip Torn, Peter Coyote, Dana Hill.
Keywords: Rawlings, Marjorie Kinnan, -- 1896-1953.; Feature films